Business rules and information systems : aligning IT with business goals - Morgan, Tony (Addison-Wesley, 2002)
Information systems often fail because their requirements are poorly defined. This book shows IT professionals how to specify more precisely and more effectively what their systems need to do. The key lies in the discovery and application of what are called business rules. A business rule is a compact and simple statement that represents some important aspect of a business. By capturing the rules for your business--the logic that governs its operation--you will gain the ability to create systems fully aligned with your business needs. In this book, Tony Morgan provides a thorough introduction to business rules, as well as a practical framework for integrating them into information systems. He shows you how to identify and express business rules, offers practical strategies for their use, and explains the key elements of logic that underpin their application. Topics covered include: Understanding the role of business rules and models in information systems development Using models to structure and manage business activities, including e-commerce Defining and discovering business rules Controlling business rule quality Fitting business rules into varied technical architectures Implementing business rules using available technology Whether you are an analyst, designer, developer, or technical manager, the in-depth information and practical perspective in this valuable resource will guide you in your efforts to build rule-centered information systems that fully support the goals of your organization. 0201743914B03042002.